E-Quran apps for armless people / Noor Izma Iffah Md Aziz … [et al.] - Md Aziz Tuan, Noor Izma Iffah; Tuan Abdullah, Nurul Ain; Abd Hamid, Nur Najah Atiqah; Mohd Sha, Nur Tysha Atikah; Jidin Noor, Aiman Zakwan; Brahin, Mohd Ariff (Division of Research and Industry Linkages, 2017)
This project proposes the development o f a PC-based Al-Quran Application which can be remotely controlled by using either a wireless remote or the reader’s face movement detection. Al-Quran, which is the book of guidance for all Muslims, is daily read either during the leisure time or during prayers. Thus, the proposed application serves to help the imams and especially the people with disability of using both hands to read it easier than the conventional ways. For armless people, the Quran pages can simply be flipped by moving the head or the face to the left or right, owing to the face detection technology. Besides, it is a user-friendly and a very low-cost application.